TAXONOMICAL IMPLICATIONS OF NATURAL COMPONENTS IN DELIMITATION OF SOME SPECIES OF ASTERACEAE FAMILY IN BAGHDAD - Rasha A. Al- Souz; H. R. H. Al-Newani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to investigate the taxonomical relationship among eight species belonging to Asteraceae based on natural products as fresh leaves of eight species (Carthamus tinctorius L., Centaurea iberica Trevir. ex Spreng., Conyza bonariensis (L.) Cronquist, Conyza canadensis (L.) Cronquist, Launaea mucronata (Forssk.) Muschl., Senecio glaucus L., Sonchus asper (L.) Hill, and Sonchus tenerrimus L.) have been collected from different regions of Baghdad. The phytochemical screening of hexane extracts from eight plants showed different secondary metabolites in the studied species. Gas chromatography-mass spectrometry (GC-MS) analysis of eight hexane extracts showed the existence of eighty-one chemical compounds of eight taxa of Asteraceae, including hydrocarbons, alcohols, organic acids, esters, amines, and heterocyclic compounds. The agglomerative hierarchical clustering analysis dendrogram was carried out depending on 81 chemical compounds of the eight taxa of Asteraceae, gained by Euclidean distance using Ward’s method. The HCA dendrogram showed the closeness of Sonchus asper and Sonchus tenerrimus and a divergence between Conyza canadensis and Conyza bonariensis and their affinity to Launaea mucronata while Carthamus tinctorius is the most divergent species from the rest of the species.